2016
DOI: 10.1037/teo0000048
|View full text |Cite
|
Sign up to set email alerts
|

Quantification in psychology: Critical analysis of an unreflective practice.

Abstract: It is common practice in psychology to presume that phenomena of interest can and should be represented numerically, and that inferences should be based on mathematical analysis of those numerical representations. In this article, we question the dominance of quantification (i.e., numerical representation) in psychological research practice. Drawing from the history of quantification in modern psychology, we argue that the motivation for quantifying information in psychology has centered on 4 related and often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 53 publications
(88 reference statements)
0
44
0
1
Order By: Relevance
“…The above results contribute to the question about adequacy of quantification of psychic phenomena. This possibility, identified with objective mode of description, contradicts subjective and reflexive nature of psychic processes [Tafreshi et al, 2016]; it is then concluded that numerical models are fundamentally incapable of expressing meaning and semantics [Brower, 1949]. Psychic phenomena of this kind are then addressed with qualitative methods [Madill and Gough, 2008] prone to the repeatability problems noted in the Introduction.…”
Section: Reflexivity Quantifiedmentioning
confidence: 99%
“…The above results contribute to the question about adequacy of quantification of psychic phenomena. This possibility, identified with objective mode of description, contradicts subjective and reflexive nature of psychic processes [Tafreshi et al, 2016]; it is then concluded that numerical models are fundamentally incapable of expressing meaning and semantics [Brower, 1949]. Psychic phenomena of this kind are then addressed with qualitative methods [Madill and Gough, 2008] prone to the repeatability problems noted in the Introduction.…”
Section: Reflexivity Quantifiedmentioning
confidence: 99%
“…These issues may have contributed to the fact that metrologists' important concerns about the limitations and challenges of 'human-based data generation' (Berglund et al, 2012;Pendrill, 2014;Pendrill & Petersson, 2016) have hardly been noted by psychological and social scientists. And this although metrologists' views can meaningfully complement and expand on the psychologists' and social scientists' increasing criticism of their own methodological practices that, so far, mostly concern the generation and analysis of quantitative data in their fields (e.g., Bruschi 2017;Buntins et al 2016;Hammersley 2013;Morris et al 2017;Tafreshi et al 2016;Valsiner 2017). A prominent controversy is the debate about so-called quantitative and qualitative methods, which revolves around the question of whether or not behavioural, psychological and social phenomena can be meaningfully explored by means of quantification, what access researchers can generally gain to these phenomena and how findings can be interpreted (e.g., Bruschi 2017;Michell 2010;Sale et al 2002;Toomela 2011).…”
Section: Jingle Jangle Fallacies Across Sciences: Are 'Measurement Inmentioning
confidence: 99%
“…Loyal adherence to CTT, the standard paradigm prescribed in measurement psychology, can be seen as the breeding ground for a long coming crisis in career assessment when the existing paradigm breaks down (Kuukkanen, ; Tafreshi, Slaney, & Neufeld, ). Sternberg and Williams () captured the challenge for career theorists very well in the following statements about the intellectual ossification in psychological assessment:…”
Section: Redefining Psychometrics For Career Guidance To Focus On Evamentioning
confidence: 99%